Assessing the Nexus Between Indonesia’s Government Bond Yields and Global Volatility Index (VIX) Sentiment - Fahmi Sahlan; Diamond Limbonb; Fitriyani; Rizki Ramadhani; fithri suciati (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
This study rigorously assesses the intricate long-run and short-run nexus between Indonesia's 10-year government bond yields and the Global Volatility Index (VIX) sentiment, using high-frequency daily data spanning the turbulent 2019–2023 period. Employing the flexible Autoregressive Distributed Lag (ARDL) model, we simultaneously analyze the impact of global volatility alongside crucial domestic macro-financial factors, namely the Bank Indonesia benchmark interest rate and the USD/IDR exchange rate. The results firmly establish a significant long-run cointegrating relationship, demonstrating that persistently elevated VIX levels positively and structurally correlate with increased bond yields, quantitatively confirming the demand for a higher sovereign risk premium by international investors during times of global uncertainty. The analysis also confirms the dominant influence of domestic factors, particularly the strong monetary policy transmission through interest rates. Crucially, the Error Correction Mechanism (ECM) reveals a rapid adjustment speed (????day), signifying the high responsiveness and efficiency of the market in incorporating both global and domestic shocks. These robust findings emphasize the critical necessity for policymakers and investors in emerging markets to systematically integrate VIX as a key macroprudential indicator into resilient sovereign debt management and strategic investment allocation frameworks.